The role of prestress and its optimization in cable domes design. (December 2015) - Quagliaroli, M.; Malerba, P.G.; Albertin, A.; Pollini, N.
Highlights: The matrix theory for pin-jointed trusses is recalled. The role of prestress is outlined and discussed. A structural optimization process based on genetic algorithms is presented. Several cable domes are analyzed, optimized and compared. Abstract: For their lightweight, versatile forms and architectural impact, cable-strut structural systems have been widely used as large span roofs of arenas, stadiums and open squares. In this paper, the matrix theory for pin-jointed trusses is firstly recalled. Then, through an elementary cable dome, the role of prestress is outlined and commented. Finally, a special optimization procedure, based on genetic algorithms, allows a thorough comparison between classical structural schemes, whose bearing capacity is due to the mechanical stiffness, and prestressed structures, whose bearing capacity is also due to the geometrical stiffness provided by the prestress.